Atheroprotective mechanisms of shear stress-regulated microRNAs - Boon, Reinier A.; Hergenreider, Eduard; Dimmeler, Stefanie (Thrombosis and Haemostasis, 2012)
MicroRNAs (miRs) are small non-coding RNAs that control gene expression by inhibiting translation or inducing degradation of targeted mRNA. miRs play a crucial role in vascular homeostasis but also during pathophysiological processes. Functionally active endothelial cells maintain homeostasis of the vasculature and protect against cardiovascular disease. The mechanical activation of endothelial cells by laminar shear stress provides a potent atheroprotective effect and reduces endothelial inflammation and cell cycle progression. Laminar shear stress induces profound changes in gene expression and recently was shown to regulate various miRs. The down-regulation of miR-92a by shear stress enhances the expression of the endothelial nitric oxide synthase, whereas the up-regulation of miR-19a contributes to the shear stress-induced inhibition of cell proliferation. In addition, members of the miR-23–27–24 cluster are increased and specifically miR-23b blocks cell cycle progression, whereas miR-27b was shown to reduce endothelial cell repulsive signals. Finally, increased miR-10 expression in atheroprotected regions reduced the inflammatory response of endothelial cells and increased endothelial miR-143/145 levels improved smooth muscle cells functions. Together, the regulation of miRs by shear stress contributes to the anti-inflammatory, cell cycle inhibitory and vasculoprotective effects in endothelial cells.
Keywords: Atherosclerosis; shear stress; angiogenesis and inhibitors; endothelial cells